Risk Factors for the Home Physical Environment and the Incidence of Childhood Tuberculosis - Nofi Susanti; Yulia Khairina Ashar; Putra Apriadi Siregar; Muhammad Rezebri; Desty Adinda; M. Iqbal (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Risk factors for tuberculosis in children include lack of nutrition, HIV infection, poverty, cigarette smoke exposure, and close contact with infected individuals. Children's immune systems are less developed, making them more susceptible and causing severe complications. This study uses cross-sectional research to analyze secondary data from Indonesia's 2018 Basic Health Research study. The sample consisted of 110.465 children aged 0-14, selected randomly or based on criteria. The study used univariate analysis and chi-square bivariate analysis to determine the relationship between variables and the incidence of tuberculosis in children. Further analyses were conducted in May-June 2024 using JASP version 16.The study revealed a significant association between lighting conditions and TB incidence, with 119 cases in well-lit master bedrooms and 51 in poorly lit bedrooms. Kitchen windows also played a role. However, the study concluded that the association could be due to chance, with no strong association between adequate living room lighting and TB incidence.The study found no significant association between lighting or ventilation conditions in different house areas and tuberculosis (TB) incidence. Although slight variations were observed, these were likely due to chance. The prevalence ratios also showed no strong association between adequate lighting or ventilation and TB incidence. Public health initiatives should focus on improving housing infrastructure, ventilation, and hygiene to mitigate environmental risk factors. Further research is recommended to explore socioeconomic and geographical variations influencing TB incidence in children. Keyword: Children, Environment, Home, Tubeculosis